Quantitative systems pharmacology model for Alzheimer's disease to predict the effect of aducanumab on brain amyloid - Lin Lin; Fei Hua; Cristian Salinas; Carissa Young; Thierry Bussiere; Joshua F. Apgar; John M. Burke; Kumar Kandadi Muralidharan; Rajasimhan Rajagovindan; Ivan Nestorov (Wiley, 2022)
Abstract Alzheimer's disease (AD) is an irreversible, progressive brain disorder that impairs memory and cognitive function. Dysregulation of the amyloid‐β (Aβ) pathway and amyloid plaque accumulation in the brain are hallmarks of AD. Aducanumab is a human, immunoglobulin gamma 1 monoclonal antibody targeting aggregated forms of Aβ. In phase Ib and phase III studies, aducanumab reduced Aβ plaques in a dose dependent manner, as measured by standard uptake value ratio of amyloid positron emission tomography imaging. The goal of this work was to develop a quantitative systems pharmacology model describing the production, aggregation, clearance, and transport of Aβ as well as the mechanism of action for the drug to understand the relationship between aducanumab dosing regimens and changes of different Aβ species, particularly plaques in the brain. The model was used to better understand the pharmacodynamic effects observed in the clinical trials of aducanumab and assist in the clinical development of future Aβ therapies.